Analisis Suatu Perlindungan Serta Pengawasan Terhadap Hukum Dalam Perspektik Hak Pada Manusia - Faturohman Faturohman; Siti Alivia Azzahra; Dody Darly (Doktrin: Jurnal Dunia Ilmu Hukum dan Politik, 2024)
Protection and supervision of the law from the perspective of human rights is something that must be realized in the justice and welfare of every individual. The existence of legal protection for this right aims to refer to a mechanism and procedure that has been provided by the state to ensure that this right can be respected and monitored. Supervision of the law, if seen on the other hand, includes several efforts to ensure that the law can be implemented as fairly as possible, without discrimination or abuse. This right to humans has the aim of protecting the dignity possessed by every human being, this right can guarantee that every person needs to be respected and their nature cannot be contested.